Copolymerized polyester resin
By controlling the content of specific oligomers in the copolyester resin and using a specific catalyst combination, the problems of die contamination, foreign matter adhesion and recovery performance are solved, and a copolyester resin with high transparency, excellent formability and good recovery performance are achieved.
Patent Information
- Application Number
- CN202380063725.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-05-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the process of producing copolyester resin, there are problems of die contamination, foreign matter adherence to the product, and the resin coloration and molecular weight decrease during recycling.
By controlling the content of free cyclic monomers and linear oligomers in the copolyester resin, it is suppressed to be less than 40 ppm and less than 60 ppm, and using a specific catalyst combination, the carboxyl terminal group concentration and additive ratio are adjusted to improve the thermal stability and recovery performance of the resin.
It realizes that there is almost no mold contamination or foreign matter adhesion when producing films, molded products, fibers and other products. At the same time, the resin coloring and molecular weight decrease are avoided during the recycling process, and the transparency and formability of the product are improved.
Smart Images

Figure BDA0005296561820000121 
Figure BDA0005296561820000131 
Figure BDA0005296561820000132
Abstract
Description
Technical Field
[0001] The present invention relates to a copolyester resin which has excellent transparency and moldability, generates almost no contamination around the die head and foreign matter adhesion when producing products such as films, and has excellent recyclability. Background Art
[0002] Polyester, especially polyethylene terephthalate (PET) produced from terephthalic acid (hereinafter sometimes referred to as TPA) and ethylene glycol (hereinafter sometimes referred to as EG) as raw materials, is widely used in containers, films, sheets, fibers, etc. due to its excellent chemical and physical properties.
[0003] In recent years, polyester resins (hereinafter sometimes referred to as copolyester resins) obtained by copolymerizing diethylene glycol (hereinafter sometimes referred to as DEG) in polyethylene terephthalate (PET) have attracted attention due to their excellent transparency, moldability, impact resistance, heat resistance, etc., and are being used for various purposes, especially as base polymers for molded bodies such as films, sheets, injection molded bodies, and heteromorphic molded bodies. At this time, in addition to terephthalic acid, an aliphatic dicarboxylic acid is further copolymerized to reduce the melting point and glass transition temperature of the obtained copolyester resin to impart flexibility, and to adjust the crystallinity and crystallization rate, depending on the application.
[0004] In addition, polyester resins (hereinafter sometimes referred to as copolyester resins) obtained by copolymerizing sodium sulfoisophthalate (hereinafter sometimes referred to as GCM) have excellent biodegradability and are therefore attracting attention and are being used for various purposes, particularly as base polymers for molded products such as films, sheets, injection molded products, and heteromorphic molded products (see Patent Documents 1 to 6).
[0005] However, when the copolyester resins produced by the techniques of Patent Documents 1 to 6 are used to continuously produce products such as films, molded products, and fibers, there are problems such as low-melting-point foreign matter adhering to the die head and the periphery of the mold, being transferred and adhering to the surface of the product, thereby reducing the product value. In addition, there are problems such as coloration of the resin and reduction of the molecular weight during recycling. Prior art literature Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-150542 Patent Document 2: Japanese Patent No. 4755995 Patent Document 3: Japanese Patent No. 4614963 Patent Document 4: Japanese Patent Application No. 2007-500769 Patent Document 5: Japanese Patent No. 4807952 Patent Document 6: Japanese Patent No. 5345749 Summary of the invention Problems to be solved by the invention
[0007] The present invention has been developed to solve the above-mentioned problems of the prior art, and its subject is to solve the problems of die contamination and foreign matter adhesion to products when continuously producing products such as films, molded products, fibers, etc. in a copolyester resin obtained by copolymerizing diethylene glycol and sodium sulfoisophthalate in order to improve transparency and formability, and to solve the problems of resin coloration and molecular weight reduction during recycling. Means of solving problems
[0008] In order to solve the above problems, the present inventors conducted in-depth research on the causes of die contamination and foreign matter adhesion to products in copolyester resins obtained by copolymerizing diethylene glycol and sodium sulfoisophthalate. As a result, it was found that specific cyclic monomers and linear oligomers (hereinafter sometimes referred to as by-product oligomers) generated as by-products during the production of copolyester resins are the causes of die contamination and foreign matter adhesion to products. By suppressing the content of these by-products to a certain value or less, a copolyester resin with almost no problems of die contamination and foreign matter adhesion to products can be provided. In addition, the inventors conducted in-depth research on the causes of resin coloration and molecular weight reduction during recycling. As a result, it was found that diethylene glycol and sodium sulfoisophthalate used as materials of copolyester resins can improve transparency and formability, but on the other hand, they reduce the thermal stability and thermal oxidation stability of the obtained copolyester resin. Therefore, it is believed that heating during film formation and molded product production deteriorates the resin, causing the film and molded product to be colored and its molecular weight to be reduced. Then, the present inventors studied methods for improving the thermal stability and thermal oxidation stability of the copolyester resin, found that it is important to control the carboxyl terminal group concentration (AV) of the copolyester resin within a certain range, and use a specific combination of two catalysts used in polymerization, and completed the present invention.
[0009] That is, the present invention is completed based on the above-mentioned findings and has the following structures (1) to (12). (1) A copolyester resin characterized in that it is a copolyester resin containing terephthalic acid as a main dicarboxylic acid component and ethylene glycol as a main diol component; in all polyester resin components, when the total amount of dicarboxylic acid components is 100 mol%, the ratio of terephthalic acid components to all dicarboxylic acid components is 79.95-94.95 mol%, the ratio of aliphatic acids having 2 to 4 carbon atoms to all dicarboxylic acid components is 5 to 20 mol%, the ratio of sodium sulfoisophthalate to all dicarboxylic acid components is 0.05 to 10 mol%, the ratio of diethylene glycol to all diol components is 1 to 22 mol%, the content of free cyclic monomers composed of terephthalic acid, sodium sulfoisophthalate and ethylene glycol is 40 ppm or less, and the content of free linear oligomers composed of terephthalic acid, sodium sulfoisophthalate and ethylene glycol is 60 ppm or less. (2) The copolyester resin according to (1), wherein the chromaticity b value is -5.0 to 15.0. (3) The copolyester resin according to (1), wherein the carboxyl terminal group concentration (AV) is 3 to 25 eq / t. (4) The copolyester resin according to (1), characterized in that the copolyester resin contains aluminum atoms and phosphorus atoms, the content of aluminum atoms in the copolyester resin is 15 to 40 ppm, and the molar ratio of phosphorus atoms to aluminum atoms in the copolyester resin is greater than 0 and less than 2.6. (5) The copolyester resin according to (1), characterized in that the copolyester resin further contains alkali metal atoms and / or alkaline earth metal atoms derived from alkali metal compounds and / or alkaline earth metal compounds other than sodium sulfoisophthalate, and the content of the alkali metal atoms and / or alkaline earth metal atoms in the copolyester resin is 1 to 100 ppm. (6) The copolyester resin according to any one of (1) to (5), wherein a step-molded plate obtained by molding the copolyester resin has a haze value of 10% or less in a portion having a thickness of 3 mm. (7) A molded article comprising the copolyester resin according to any one of (1) to (5). (8) A heat shrinkable film comprising the copolyester resin according to any one of (1) to (5). (9) A fiber characterized by comprising the copolyester resin according to any one of (1) to (5). (10) A nonwoven fabric comprising the copolyester resin according to any one of (1) to (5). (11) An adhesive comprising the copolyester resin according to any one of (1) to (5). (12) A coating material comprising the copolyester resin according to any one of (1) to (5). Effects of the Invention
[0010] The copolymerized polyester resin of the present invention has the advantages of transparency and formability brought about by the use of diethylene glycol and sodium sulfoisophthalate, and when continuously producing products such as films, molded products, fibers, etc., there is almost no die contamination and foreign matter adhesion to the products. In addition, there is no resin coloring and molecular weight reduction during recycling. DETAILED DESCRIPTION
[0011] The copolyester resin of the present invention is described in detail below. The copolyester resin of the present invention is a resin obtained by copolymerizing diethylene glycol and sodium sulfoisophthalate in a copolyester resin containing terephthalic acid as a main dicarboxylic acid component and ethylene glycol as a main diol component for the sake of transparency and moldability. The content of specific cyclic monomers and linear oligomers generated as by-products during polymerization is suppressed to a certain value or less, thereby effectively preventing problems such as die contamination and foreign matter adhesion to the product. Furthermore, by controlling the carboxyl terminal group concentration (AV) of the copolyester resin within a certain range and using a specific combination of two catalysts used in polymerization, problems such as resin coloration and molecular weight reduction during recycling are effectively prevented.
[0012] The copolyester resin of the present invention contains terephthalic acid as a main dicarboxylic acid component. Specifically, as the content of terephthalic acid, when the total amount of dicarboxylic acid components is 100 mol%, the ratio of terephthalic acid to the total dicarboxylic acid components is 79.95 to 94.95 mol%, preferably 85 to 94.95 mol%, and more preferably 90 to 94.95 mol%.
[0013] The copolyester resin of the present invention further contains an aliphatic acid having 2 to 4 carbon atoms as a dicarboxylic acid component in addition to terephthalic acid. The aliphatic acid having 2 to 4 carbon atoms has the effect of lowering the melting point and glass transition temperature of the obtained copolyester resin, imparting flexibility, and adjusting the crystallinity and crystallization rate. Examples of the aliphatic acid having 2 to 4 carbon atoms include oxalic acid (carbon number 2), malonic acid (carbon number 3), and succinic acid (carbon number 4). The content of the aliphatic acid having 2 to 4 carbon atoms can be appropriately adjusted according to the use of the copolyester resin. When the total amount of the dicarboxylic acid component is 100 mol%, the ratio of the aliphatic acid having 2 to 4 carbon atoms to the total dicarboxylic acid component is usually 5 to 20 mol%, preferably 7 to 18 mol%, and more preferably 8 to 15 mol%. The more the content of the aliphatic acid having 2 to 4 carbon atoms increases, the lower the melting point, glass transition temperature, crystallinity, and crystallization rate of the obtained copolyester resin tend to be.
[0014] The copolyester resin of the present invention contains sodium sulfoisophthalate as a dicarboxylic acid component in addition to terephthalic acid and an aliphatic acid having 2 to 4 carbon atoms in order to improve biodegradability. Specifically, as the content of sodium sulfoisophthalate, when the total amount of dicarboxylic acid components is 100 mol%, the ratio of sodium sulfoisophthalate to the total dicarboxylic acid components is 0.05 to 10 mol%, preferably 0.1 to 5 mol%, and more preferably 0.2 to 3 mol%. When the content of sodium sulfoisophthalate is less than the above lower limit, the haze value tends to be high and the DSC measurement is poor. On the other hand, when the content of sodium sulfoisophthalate is greater than the above upper limit, the amount of free cyclic monomers and linear oligomers described later increases, and die contamination and foreign matter adhesion to the product increase.
[0015] The copolyester resin of the present invention may contain other dicarboxylic acid components other than terephthalic acid, aliphatic acid having 2 to 4 carbon atoms and sodium sulfoisophthalate. Examples of the other dicarboxylic acid components include (1) aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, and diphenoxyethane dicarboxylic acid, and their functional derivatives; and (2) alicyclic dicarboxylic acids such as hexahydroterephthalic acid, hexahydroisophthalic acid, and cyclohexane dicarboxylic acid, and their functional derivatives.
[0016] The copolyester resin of the present invention contains ethylene glycol as a main component of the diol component. Specifically, as the content of ethylene glycol, when the total amount of the diol component is set to 100 mol%, the ratio of ethylene glycol to the total diol component is preferably 50 to 99 mol%, more preferably 70 to 99 mol%, further preferably 80 to 99 mol%, and particularly preferably 90 to 99 mol%.
[0017] In addition to ethylene glycol, the copolyester resin of the present invention contains diethylene glycol as a glycol component in order to improve transparency and formability. Specifically, as the content of diethylene glycol, when the total amount of glycol components is set to 100 mol%, the ratio of diethylene glycol to all glycol components is 1 to 22 mol%, preferably 1 to 20 mol%, and more preferably 1 to 18 mol%. By making the content of diethylene glycol within the above range, a copolyester resin with high transparency, i.e., amorphous, can be obtained. When the content of diethylene glycol is less than the above lower limit, the transparency of the molded product and the film deteriorates due to crystallinity, and sufficient transparency tends to be unable to be achieved, and there is no commercial value. On the other hand, when the content of diethylene glycol is greater than the above upper limit, the recyclability (thermal stability) tends to decrease, the resin is colored, and the AA content increases.
[0018] Diethylene glycol is also formed by condensation of ethylene glycol during polymerization of the copolyester resin. The amount of diethylene glycol generated by this condensation varies depending on the polymerization conditions and the manufacturing apparatus, but is about 0.5 to 2.0 mol% relative to the total diol components. This amount can be taken into account when considering the amount of diethylene glycol added as a raw material.
[0019] In addition, the amorphous property here means that the sample left at 120°C for 120 minutes in a YAMATO DP63 dryer has no melting peak in any of the processes of heating from -100°C to 300°C at 20°C / min, cooling to -100°C at 50°C / min, and then heating from -100°C to 300°C at 20°C / min using a differential scanning calorimeter (DSC). Since the copolyester resin of the present invention is amorphous, it can have transparency that can be used appropriately even for a particularly thick molded body. That is, the so-called "amorphous property" in the present measurement conditions means that the transparency of the film can be maintained at a high quality, and further, sufficient transparency can be maintained even when a thick film is formed.
[0020] The copolyester resin of the present invention may contain other diol components besides ethylene glycol and diethylene glycol. Examples of the other diol components include (1) aliphatic diols such as tetramethylene glycol, pentamethylene glycol, and hexamethylene glycol, (2) alicyclic diols such as 1,3-cyclohexanedimethanol and 1,4-cyclohexanedimethanol, and (3) aromatic diols such as p-xylylene glycol and m-xylylene glycol.
[0021] In order to improve the profile extrusion moldability, the copolyester resin of the present invention preferably contains a polyfunctional compound having three or more carboxyl groups, hydroxyl groups or their ester-forming groups (e.g., trimellitic acid, pyromellitic acid, glycerol, trimethylolpropane, etc.) in an amount of 0.001 to 5 mol % of the acid component and / or diol component of the copolyester resin.
[0022] The essential feature of the copolyester resin of the present invention is that the content of specific cyclic monomers and linear oligomers generated as by-products during polymerization is suppressed to below a certain value, thereby effectively preventing the problems of die contamination and foreign matter adhesion to the product. Specifically, in the copolyester resin of the present invention, the content of free cyclic monomers composed of terephthalic acid, sodium sulfoisophthalate, and ethylene glycol is 40 ppm or less, and the content of free linear oligomers composed of terephthalic acid, sodium sulfoisophthalate, and ethylene glycol is 60 ppm or less. In the present invention, the free cyclic monomer composed of terephthalic acid, sodium sulfoisophthalate, and ethylene glycol refers to a cyclic monomer in which terephthalic acid, sodium sulfoisophthalate, sodium sulfoisophthalate, ethylene glycol, ethylene glycol, and ethylene glycol are bonded in this order to form a ring (hereinafter referred to as TS2E3), and the linear oligomer composed of terephthalic acid, sodium sulfoisophthalate, and ethylene glycol refers to a linear oligomer in which terephthalic acid, terephthalic acid, sodium sulfoisophthalate, ethylene glycol, ethylene glycol, ethylene glycol, and ethylene glycol are bonded in this order to form a ring (hereinafter referred to as L-T2SE4). In addition, in the present invention, the "copolyester resin" refers to a resin containing oligomer components called TS2E3 and L-T2SE4 or a catalyst component described later in addition to a chemical substance called polyester. When explaining a chemical substance called polyester, it may be described as a "copolyester resin" for convenience.
[0023] The content of TS2E3 needs to be 40ppm or less, preferably 35ppm or less, and more preferably 30ppm or less. When it is greater than the above upper limit, the pollution near the resin outlet of the extrusion molding machine die head becomes serious when producing films and fibers, and the attached foreign matter adheres to the surface of the molded body, the surface state deteriorates, and the transparency is also affected, resulting in a decrease in the value of the product. In addition, the continuous injection molding of the molded product will cause the exhaust port of the injection molding mold to be blocked, and a normal molded product cannot be obtained. In addition, for economic considerations during production, the lower limit of the content is 1ppm. The content of TS2E3 is a value quantified by the determination method of the embodiments described later.
[0024] The content of L-T2SE4 needs to be less than 60ppm, preferably less than 55ppm, and more preferably less than 50ppm. When greater than the above upper limit, the pollution near the resin outlet of the extrusion molding machine die head tends to become serious when producing films and fibers, and the attached foreign matter adheres to the surface of the molded body, the surface state deteriorates, affects the transparency, and the commodity value decreases. In addition, the continuous injection molding of the molded product will cause the exhaust port of the injection molding mold to be blocked, and a normal molded product cannot be obtained. In addition, for economic considerations during production, the lower limit of the content is 1ppm. The content of L-T2SE4 is a value quantitatively determined by the determination method of the embodiments described later.
[0025] Although the mechanism of contamination and foreign matter adhesion around the die caused by L-T2SE4 and TS2E3 is unclear, it is considered that due to the steric hindrance of ethylene glycol and sulfoisophthalic acid in L-T2SE4, the melting point and glass transition temperature of L-T2SE4 are lowered. Furthermore, due to the steric hindrance of ethylene glycol and sulfoisophthalic acid in TS2E3, the melting point and glass transition temperature of TS2E3 are lower than those of L-T2SE4, so that stronger adhesion is exhibited. Due to the synergistic effect of TS2E3 and L-T2SE4, the adhesion to the die of the film extrusion molding machine during molding is increased.
[0026] The copolyester resin of the present invention preferably has a carboxyl terminal group concentration of 3 to 25 equivalents per ton of polymer, more preferably 5 to 23 equivalents per ton. By setting the carboxyl terminal group concentration within the above range, it can help suppress the coloring of the copolyester resin. In the case where the coloring of the copolyester resin is slightly less acceptable, the carboxyl terminal group concentration may be 32 equivalents per ton or less. Considering productivity (reaction time), the lower limit of the carboxyl terminal group concentration may be 0 equivalent per ton.
[0027] The number average molecular weight of the copolyester resin of the present invention is preferably 2000 to 30000, more preferably 2500 to 28000, and further preferably 3000 to 27000. When the number average molecular weight is less than the above lower limit, the crystallinity is increased and the haze is increased. Furthermore, due to insufficient resin cohesion, the tensile strength and elongation of the molded product are insufficient, and there is a case where it becomes brittle and cannot be used. On the other hand, when it is greater than the above upper limit, due to excessively high melt viscosity, the most suitable temperature for various molding processes is also increased, the residence time is increased, and the film-forming property of the sheet is decreased. Furthermore, the amount of the above TS2E3 and L-T2SE4 increases, and there is a case where the transparency of the molded body is deteriorated due to die contamination and foreign matter adhesion.
[0028] The glass transition temperature of the copolyester resin of the present invention is preferably 40°C or more and less than 120°C, more preferably 45°C or more and less than 115°C, further preferably 50°C or more and less than 110°C, and particularly preferably 50°C or more and less than 70°C. Here, the glass transition temperature refers to a value measured by heating at 20°C / min using a differential scanning calorimeter (DSC). When the glass transition temperature is less than the above lower limit, when the profiled extrusion molding is used outdoors in summer, or when the product is transported or stored in a warehouse in a closed state in summer, the film or profiled extrusion molding may be thermally deformed. In addition, when the glass transition temperature is greater than the above upper limit, the film-forming property and transparency of the sheet tend to decrease, and it may not be usable depending on the application.
[0029] The chromaticity b value of the copolyester resin of the present invention is preferably -5.0 to 15.0. The lower limit of the chromaticity b value is more preferably -3.0, and further preferably -2.5. In addition, the upper limit is more preferably 14.0, and further preferably 13.0. When the chromaticity b value is greater than the above upper limit, the yellow hue of the copolyester resin becomes stronger, which is not preferred in terms of color tone. On the other hand, when the chromaticity b value is less than the above lower limit, the blue hue of the copolyester resin becomes conspicuous, and it may not be used depending on the application.
[0030] The copolyester resin of the present invention preferably has a haze value of 10% or less, more preferably 9% or less, and particularly preferably 8% or less in a thickness of 3 mm of a step-shaped molded plate (step-shaped molded plate) molded at a mold temperature of 10° C. If the haze value exceeds the upper limit, the transparency of the molded article or film deteriorates, and the molded article or film may not be used in applications requiring strict transparency.
[0031] The copolyester resin of the present invention may be added with other components as appropriate according to the application. For example, impact resistance enhancers, fillers, ultraviolet absorbers, surface treatment agents, lubricants, light stabilizers, pigments, antistatic agents, antibacterial agents, crosslinking agents, sulfur antioxidants, flame retardants, plasticizers, processing aids, foaming agents, etc. may be added. The copolyester of the present invention is preferably formed into various molded bodies by extrusion blow molding, deep drawing molding, injection molding, profile extrusion molding, rolling processing molding, etc., which are commonly used in PET and the like.
[0032] The copolyester resin of the present invention can be preferably used in various applications requiring transparency, moldability, etc., and can be used as a raw material for molded products, heat shrinkable films, fibers, nonwoven fabrics, adhesives, coatings, and the like.
[0033] The following is an explanation of the method for producing the copolyester resin of the present invention. The copolyester resin of the present invention can be produced by a production method based on a direct esterification reaction and a polycondensation reaction, or a production method based on an ester exchange reaction and a polycondensation reaction. The above reaction can be carried out using a continuous reaction device or a batch reaction device. From the perspective of economy and quality stability, the method using a continuous reaction device is preferred.
[0034] In the continuous reaction apparatus (continuous polycondensation method), the esterification reaction, the transesterification reaction and the melt polycondensation reaction can each be carried out in one stage, but preferably in multiple stages. When the esterification reaction or the transesterification reaction is divided into multiple stages, the number of reaction tanks is preferably 2 to 3 tanks. In addition, when the melt polycondensation is divided into multiple stages, the number of reaction tanks is preferably 3 to 7 tanks.
[0035] When the copolyester resin of the present invention is manufactured by a continuous polycondensation method, a slurry containing 1.02 to 1.5 moles, preferably 1.03 to 1.4 moles of all diols is prepared relative to 1 mole of all dicarboxylic acids or their ester derivatives, and it is continuously supplied to the esterification reaction step containing oligomers. The esterification reaction temperature is usually 240 to 270°C, preferably 250 to 265°C. In addition, the pressure in the reaction tank is usually 0.2MPa or less, preferably 0.01 to 0.05MPa. In addition, the temperature of the polycondensation reaction is usually 265 to 285°C, preferably 270 to 280°C, and the pressure in the reaction tank is usually 1.5hPa or less, preferably 0.5hPa or less. The reaction time of the esterification reaction is preferably 5 hours or less, and particularly preferably 2 to 3.5 hours. In addition, the reaction time of the polycondensation reaction is preferably 3 hours or less, and particularly preferably 1 to 2 hours.
[0036] When the copolyester resin of the present invention is manufactured by an intermittent polycondensation method, the esterification reaction temperature is usually 220 to 250°C, preferably 230 to 245°C. In addition, the pressure in the reaction tank is usually 0.2 to 0.4 MPa, preferably 0.25 to 0.30 MPa. In addition, the polycondensation reaction can be carried out in one stage or in multiple stages. When carried out in one stage, the pressure is gradually reduced and the temperature is increased, and the final temperature is set to 260 to 280°C, preferably in the range of 265 to 275°C, and the final pressure is usually set to less than 3 hPa, preferably less than 0.5 hPa. The reaction time of the esterification reaction is preferably less than 4 hours, and particularly preferably 2 to 3 hours. In addition, the reaction time of the polycondensation reaction is preferably less than 5 hours, and particularly preferably 1 to 3 hours.
[0037] Then, when producing the oligocondensate by continuous transesterification, a solution containing dimethyl terephthalate and 1.1 to 1.6 mol, preferably 1.2 to 1.5 mol of diol per 1 mol of dimethyl terephthalate is prepared, and the solution is continuously supplied to the transesterification step. The transesterification temperature is usually 200 to 270° C., preferably 230 to 265° C. In the case of the transesterification method, in addition to the polycondensation catalyst, a transesterification catalyst is required. The obtained oligocondensate is reacted in the same manner as the above-mentioned continuous polycondensation.
[0038] When producing a low polycondensate by a batch transesterification reaction, dimethyl terephthalate and 2.3 to 2.0 mol, preferably 2.2 to 2.0 mol, of a diol per mol of dimethyl terephthalate are added to a batch reactor and reacted in the presence of a transesterification catalyst. The obtained low polycondensate is polycondensed in the same manner as in the above-mentioned esterification reaction.
[0039] As the polycondensation catalyst, at least one of an antimony compound, a germanium compound, a titanium compound, and an aluminum compound can be used. Examples of the antimony compound include antimony trioxide, antimony pentoxide, antimony acetate, and antimony glycol. Among these, antimony trioxide, antimony acetate, and antimony glycol are preferred, and antimony trioxide is particularly preferred. These antimony compounds preferably contain 50 to 400 ppm, more preferably 100 to 350 ppm, and particularly preferably 150 to 300 ppm of antimony element relative to the generated copolyester resin.
[0040] In addition, as the above-mentioned germanium compound, for example, crystalline germanium dioxide, amorphous germanium dioxide, germanium tetraoxide, germanium hydroxide, germanium oxalate, germanium chloride, tetraethoxygermanium, tetra-n-butoxygermanium, germanium phosphite and the like can be cited. Among these, crystalline germanium dioxide and amorphous germanium dioxide are more preferred, and amorphous germanium dioxide is particularly preferred. These germanium compounds preferably contain 10 to 100 ppm, more preferably 30 to 70 ppm, and particularly preferably 30 to 50 ppm of germanium element relative to the generated copolyester resin.
[0041] In addition, as the titanium compound, for example, tetraalkyl titanates such as tetraethyl titanate, tetraisopropyl titanate, tetra-n-propyl titanate, and tetra-n-butyl titanate and partial hydrolyzates thereof, titanium oxalate compounds such as titanium acetate, titanium oxalate, ammonium titanium oxalate, sodium titanium oxalate, potassium titanium oxalate, calcium titanium oxalate, and strontium titanium oxalate, titanium trimellitate, titanium sulfate, titanium chloride, hydrolyzates of titanium halides, titanium bromide, titanium fluoride, potassium hexafluorotitanate, ammonium hexafluorotitanate, cobalt hexafluorotitanate, manganese hexafluorotitanate, titanium acetylacetonate, titanium complexes with hydroxy polycarboxylic acids or nitrogen-containing polycarboxylic acids, composite oxides composed of titanium and silicon or zirconium, and reaction products of alkoxytitanium and phosphorus compounds, etc. Among these, tetraisopropyl titanate, tetrabutyl titanate, and potassium titanium oxalate are preferred, and tetrabutyl titanate is particularly preferred. The content of these titanium compounds is preferably 1 to 50 ppm, more preferably 2 to 20 ppm, and particularly preferably 3 to 10 ppm, in terms of titanium element, based on the produced copolyester resin.
[0042] As the polycondensation catalyst, aluminum compounds are particularly preferred from the perspective of recyclability (heat resistance, thermal oxidation stability). The aluminum compound is preferably used in combination with a phosphorus compound. As the aluminum compound constituting the polymerization catalyst used when manufacturing the copolyester resin of the present invention, known aluminum compounds can be used without limitation.
[0043] Specific examples of aluminum compounds include aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, basic aluminum chloride, aluminum acetylacetonate, aluminum oxalate and other organic aluminum compounds and partial hydrolyzates thereof. Among these, carboxylates, inorganic acid salts and chelate compounds are preferred, among these, aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, basic aluminum chloride and aluminum acetylacetonate are more preferred, aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide and basic aluminum chloride are further preferred, and aluminum acetate and basic aluminum acetate are most preferred.
[0044] The amount of the aluminum compound used in the polymerization catalyst is preferably 15 to 40 ppm, more preferably 17 to 38 ppm, and further preferably 20 to 35 ppm, in terms of aluminum atoms, relative to the total mass of the obtained polyester resin. When the residual amount of aluminum atoms is less than the above range, the catalyst activity may be poor. On the other hand, when the residual amount of aluminum atoms is greater than the above range, thermal stability and thermal oxidation stability may decrease, or the generation of foreign matter and increased coloring due to aluminum may become a problem. In addition, as described above, since the amount of aluminum compound used as a polymerization catalyst remains almost 100% even when placed under a reduced pressure environment during polyester polymerization, it can be considered that the amount used is the residual amount. In the case where the properties of the copolyester resin can be slightly sacrificed, the content of aluminum atoms in the copolyester resin may also be 9 to 42 ppm.
[0045] The phosphorus compound used in the polymerization catalyst is not particularly limited, but phosphonic acid compounds and phosphinic acid compounds are preferably used because they have a greater effect of improving the catalyst activity. Among these, phosphonic acid compounds are preferably used because they have a particularly greater effect of improving the catalyst activity.
[0046] Among these phosphorus compounds, when using a phosphorus compound having a phenolic moiety in the same molecule, the improvement effect of the thermal stability and thermal oxidation stability of the resin is large, so it is preferred. As long as it is a phosphorus compound with a phenolic structure, there is no particular limitation, but when using a compound having a phenolic moiety in the same molecule and selected from one or more of phosphonic acid compounds and phosphinic acid compounds, the improvement effect of the catalyst activity and the improvement effect of the thermal stability and thermal oxidation stability of the resin are both large, so it is preferred. Among these, when using one or more phosphonic acid compounds having a phenolic moiety in the same molecule, the improvement effect of the catalyst activity and the improvement effect of the thermal stability and thermal oxidation stability of the resin are both particularly large, so it is preferred.
[0047] Examples of the phosphorus compound having a phenolic moiety in the same molecule include compounds represented by the following general formulae (1) and (2).
[0048] P(=O)R 1 (OR 2 )(OR 3) General formula (1) General formula (1)
[0049] P(=O)R 1 R 4 (OR 2 ) General formula (2) General formula (2)
[0050] (In general formulas (1) to (2), R 1 R represents a hydrocarbon group having 6 to 50 carbon atoms containing a phenolic moiety, or a hydrocarbon group having 6 to 50 carbon atoms containing a substituent such as a hydroxyl group, a halogen atom, an alkoxy group, or an amino group as well as a phenolic moiety. 4 R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms which has a substituent such as a hydroxyl group, a halogen atom, an alkoxy group, or an amino group. 2 , R 3 Each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group or an alkoxy group. The hydrocarbon group may contain a branched structure, an alicyclic structure such as a cyclohexyl group, or an aromatic ring structure such as a phenyl group or a naphthyl group. 2 With R 4 The ends of the two groups can also be bonded.)
[0051] Examples of the phosphorus compound having a phenolic moiety in the same molecule include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonic acid, diethyl p-hydroxyphenylphosphonic acid, diphenyl p-hydroxyphenylphosphonic acid, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinic acid, phenyl bis(p-hydroxyphenyl)phosphinic acid, p-hydroxyphenylphenylphosphinic acid, methyl p-hydroxyphenylphenylphosphinic acid, phenyl p-hydroxyphenylphenylphosphinic acid, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinic acid, and phenyl p-hydroxyphenylphosphinic acid. In addition, examples of the phosphorus compound represented by the following general formula (3) include:
[0052]
[0053] In the general formula (3), X1 and X2 independently represent hydrogen, an alkyl group having 1 to 4 carbon atoms, or a metal having a valency of 1 or more. In addition, the metal of X1 may be divalent or more, and X2 may not be present. Furthermore, an anion having a valence corresponding to the remaining valence of the metal may be disposed with respect to the phosphorus compound. As the metal, Li, Na, K, Ca, Mg and Al are preferred.
[0054] When these phosphorus compounds having a phenolic moiety in the same molecule are added during polyester polymerization, the catalyst activity of the aluminum compound is improved, and the thermal stability and thermal oxidation stability of the polymerized polyester resin are also improved. The reason for this is considered to be that the hindered phenol moiety in the phosphorus compound improves the thermal stability and thermal oxidation stability of the polyester resin. In this case, when the residual amount of the phosphorus compound is less than 31 ppm, the above-mentioned effect of improving the thermal stability and thermal oxidation stability is small, and as a result, the improvement effect of the thermal stability and thermal oxidation stability of the polyester resin of the present invention and the improvement effect of coloration may not be observed.
[0055] Among the above, the phosphorus compound preferably used as the polycondensation catalyst is at least one phosphorus compound selected from the group consisting of compounds represented by the following chemical formula (4) and chemical formula (5).
[0056]
[0057]
[0058] As the compound represented by the above chemical formula (4), Irganox 1222 (manufactured by BASF) is commercially available. As the compound represented by the chemical formula (5), commercially available Irganox 1425 (manufactured by BASF) can be used.
[0059] The amount of the phosphorus compound used in the polymerization catalyst is preferably 31 to 104 ppm in terms of phosphorus atoms relative to the total mass of the obtained copolyester resin, more preferably 39 to 102 ppm, and further preferably 48 to 92 ppm. When it is less than the above lower limit, the effect of improving thermal stability and thermal oxidation stability may become smaller. On the other hand, when it is greater than the above upper limit, the polymerization activity may be reduced. In addition, as described above, since the phosphorus compound is placed in a reduced pressure environment during the polymerization of the polyester resin, part of the amount initially added to the system as a catalyst is removed to the outside of the system, but since the removal amount is almost a fixed ratio, it can be said that it is appropriate to specify it by the residual amount after considering the removal ratio. In the case where the properties of the copolyester resin can be slightly sacrificed, the content of phosphorus atoms in the copolyester resin can also be 19 to 125 ppm. The thermal stability is good when it is 0.7 or less, preferably 0.6 or less, and most preferably 0.5 or less.
[0060] In addition, as described above, in the present invention, the ratio of the phosphorus compound to the aluminum compound is also important. Specifically, in the present invention, the molar ratio of phosphorus atoms to aluminum atoms in the polyester resin (P / Al ratio) is preferably greater than 0 and less than 2.6, more preferably 0.2 to 2.4, and further preferably 0.4 to 2.3. When an aluminum compound is used alone as a polymerization catalyst, the catalytic activity cannot be fully exerted. In addition to the aluminum compound, by using a phosphorus compound as a polymerization catalyst in a specific ratio, the catalytic activity can be fully improved. When the molar ratio of phosphorus atoms to aluminum atoms in the polyester resin is outside the above range, it may not be able to fully play the role of a polymerization catalyst.
[0061] In the present invention, in addition to the above-mentioned aluminum compounds and phosphorus compounds, within the range that does not impair the effects of the present invention, in order to further improve the catalyst activity, a polycondensation catalyst containing metals such as titanium compounds, tin compounds, and germanium compounds may also be used in combination. In this case, the germanium compound is preferably calculated as a germanium atom of 10 ppm or less relative to the mass of the obtained polyester resin, the titanium compound is preferably calculated as a titanium atom of 3 ppm or less relative to the mass of the obtained polyester resin, and the tin compound is preferably calculated as a tin atom of 3 ppm or less relative to the mass of the obtained polyester resin. Among them, from the purpose of the present invention, it is preferred not to use these polycondensation catalysts containing metals such as titanium compounds, tin compounds, and germanium compounds as much as possible. In addition, since the antimony compounds commonly used as polymerization catalysts have poor effects on improving the thermal stability and thermal oxidation stability of the resin as described above, it is appropriate to control their use in the present invention.
[0062] In addition, in the manufacture of the copolyester resin of the present invention, in order to increase the polymerization activity or reduce the acetaldehyde (hereinafter sometimes referred to as AA) content in the manufactured copolyester resin to improve the odor, an alkali metal compound and / or an alkaline earth metal compound may be used in combination. AA is a component generated as a by-product when synthesizing the copolyester resin. Examples of the alkali metal compound and / or alkaline earth metal compound include compounds of lithium, sodium, potassium, rubidium, cesium, francium, calcium, strontium, barium, radium, beryllium, and magnesium, preferably compounds of lithium, sodium, potassium, calcium, and magnesium, more preferably compounds of lithium, sodium, and potassium, and most preferably compounds of lithium and potassium. Specific examples of the alkali metal compound and / or alkaline earth metal compound include carboxylates, alcoholates, and the like of acetates (e.g., lithium acetate) of these elements. These can be added to the reaction system in the form of powders, aqueous solutions, ethylene glycol solutions, and the like. The amount of the alkali metal compound and / or alkaline earth metal compound used is preferably such that the content of the alkali metal element and / or alkaline earth metal element (e.g., lithium element) in the copolyester resin is 0.1 to 100 ppm, more preferably 0.1 to 60 ppm, and most preferably 0.1 to 50 ppm. In addition, this content is a value excluding the content of the sodium element derived from sodium sulfoisophthalate contained as a dicarboxylic acid component in the copolyester resin of the present invention. When the content of the alkali metal element and / or alkaline earth metal element in the copolyester resin exceeds 100 ppm, thermal stability tends to decrease. On the other hand, the content of AA in the polyester resin is preferably 150 ppm or less, more preferably 120 ppm, further preferably 110 ppm or less, and most preferably 80 ppm or less. When the content of AA exceeds 150 ppm, odor tends to decrease.
[0063] In the case of direct esterification, the polycondensation catalyst can be added at any time point before the start of the esterification reaction or after the pressure esterification reaction is completed and before the start of the initial polycondensation reaction. However, when an antimony compound or a titanium compound is used as the polycondensation catalyst, it is preferably added before the esterification reaction. In addition, other polycondensation catalysts, heat stabilizers, and additives are preferably added after the esterification reaction.
[0064] In addition, in the case of the transesterification method, the above-mentioned polycondensation catalyst can be added at any time point before the start of the transesterification reaction to the start of the initial polycondensation reaction. However, since the titanium compound not only has the effect of a polycondensation catalyst, but also has the effect of a transesterification catalyst, it is preferably added before the start of the transesterification reaction. In addition, other polycondensation catalysts, heat stabilizers, and additives are preferably added after the end of the transesterification reaction. As the transesterification catalyst, titanium compounds such as manganese acetate, magnesium acetate, and tetrabutoxytitanium are preferred. The transesterification catalyst needs to be added before the start of the transesterification reaction.
[0065] In addition, when a catalyst other than the above-mentioned aluminum compound is used, a phosphorus compound can be used as a stabilizer. As the phosphorus compound, for example, phosphoric acid, phosphorous acid, phosphonic acid and their derivatives can be listed. As preferred specific examples, phosphoric acid, trimethyl phosphate, tributyl phosphate, triphenyl phosphate, monomethyl phosphate, dimethyl phosphate, monobutyl phosphate, dibutyl phosphate, phosphorous acid, trimethyl phosphite, tributyl phosphite, methylphosphonic acid, dimethyl methylphosphonate, dimethyl ethylphosphonate, dimethyl phenylphosphonate, diethyl phenylphosphonate, diphenyl phenylphosphonate can be listed. Among these, trimethyl phosphate and phosphoric acid are particularly preferred. These phosphorus compounds preferably contain 1 to 100 ppm relative to the generated copolyester, more preferably 3 to 70 ppm, and particularly preferably 5 to 50 ppm.
[0066] In order to improve the color tone of the copolyester resin, a cobalt compound can be added. By adding the cobalt compound, the chromaticity b value can be particularly reduced. The cobalt compound preferably contains 0.5 to 30 ppm, more preferably 1 to 20 ppm, and particularly preferably 1 to 15 ppm in terms of cobalt atoms relative to the copolyester resin. When the content of cobalt atoms is greater than the above range, the copolyester resin turns black, the blue tone becomes stronger, the chromaticity L value is less than 50, the chromaticity b value is less than -5, and the commercial value decreases due to the reduction of the cobalt metal. Examples of the cobalt compound include cobalt acetate, cobalt chloride, cobalt benzoate, cobalt chromate, and the like. Among these, cobalt acetate is preferred.
[0067] The copolyester resin obtained by the above-mentioned continuous polycondensation method or batch polycondensation method is usually extracted in the form of a strand from an extraction port provided at the bottom of a reaction tank, and after water cooling, is cut into small pieces or sheets.
[0068] The copolyester resin having a low content of free TS2E3 and L-T2SE4, which is the essential feature of the present invention, can be produced by the following methods: a method of simultaneously performing transesterification and esterification, a method of adding a specific diol component during or after the esterification reaction or transesterification reaction and performing a polycondensation reaction. Among them, the latter method, i.e., a method of adding a specific diol component during or after the esterification reaction or transesterification reaction and performing a polycondensation reaction, is preferred, and the specific diol component is preferably diethylene glycol or ethylene glycol, and more preferably diethylene glycol. For example, the raw material monomers taking into account the additional amount are first subjected to esterification or transesterification, diethylene glycol is added after the reaction, and polycondensation is carried out after stirring for more than 5 minutes. The additional diethylene glycol component is preferably 7.5 to 30 mol% of the total diethylene glycol component. Alternatively, the raw material monomers with the additional amount to be added may be subjected to an esterification reaction or an ester exchange reaction, diethylene glycol may be added during the reaction, and diethylene glycol may be further added after the reaction, and the mixture may be stirred for more than 5 minutes before polycondensation. The additional diethylene glycol component is preferably 5 to 20 mol% of the total diethylene glycol component. Furthermore, the raw material monomers taking into account the additional amount are first subjected to an esterification reaction or an ester exchange reaction, diethylene glycol is added during the reaction, and diethylene glycol is further added after the reaction, and after stirring for more than 5 minutes, polycondensation is performed. The additional diol (diethylene glycol + ethylene glycol) component is preferably 7.5 to 30 mol% of the total diol (diethylene glycol + ethylene glycol) component. Furthermore, TS2E3 can also be reduced by extracting in a linear form, cooling with water, and then exposing the small pieces or sheets of sheared material to the vapor of diethylene glycol or triethylene glycol for a certain period of time. Although the detailed principle is unknown, it is believed that the vapor of diethylene glycol or triethylene glycol causes the ring-shaped TS2E3 to open.
[0069] The polyester resin composition of the present invention may contain various additives as needed within the range that does not impair the characteristics of the present invention. As additives, for example, colorants such as pigments, toners, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, plasticizers, modifiers, antistatic agents, flame retardants, dyes, etc. can be listed. In order to improve the colorability of the polyester resin composition, titanium oxide and toners are preferred. The addition amount of titanium oxide is 0 to 20000ppm, preferably 0.1ppm to 15000ppm, and more preferably 0.2ppm to 13000ppm. The addition amount of toner is 0.1ppm to 100ppm, preferably 0.5 to 90ppm, and most preferably 1 to 80ppm. As toners, phthalocyanine and distyryl bisbenzoxazole derivatives can be used. Specifically, it is SOLVAPERM BLUE RLS, PVfastBLUE A4R, Hostalux KS manufactured by Clariant, or OB-1 manufactured by Eastman Kodak Company, and the like, among which the SolventBlue series manufactured by Clariant, which starts to melt at 250° C. or above and ends melting at about 300° C., is particularly preferred. Since the above-mentioned toner has the same melting point as the melting point of polyester itself (230 to 265° C.), it has very good solubility in mixing with polyester, excellent melting uniformity in a melting machine, and good spinning operability. Example
[0070] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited to the embodiments of these Examples and can be appropriately modified without departing from the gist of the present invention. In addition, the evaluation of the characteristic values in the Examples was based on the following methods.
[0071] (1) Composition ratio of copolyester resin About 5 mg of the copolyester resin sample was dissolved in 0.7 ml of a mixed solution of deuterated chloroform and trifluoroacetic acid (volume ratio 9 / 1). 1 The composition ratio was determined by H-NMR (manufactured by Varian, UNITY50).
[0072] (2) TS2E3 content 50 mg of the copolyester resin was dissolved in 1 mL of a hexafluoroisopropanol / chloroform mixture (volume ratio = 1 / 9), and 4 mL of chloroform was further added for dilution. 10 mL of methanol was added thereto to precipitate the polymer, and then centrifuged. The supernatant after centrifugation was concentrated to dryness and redissolved in 0.4 mL of dimethylformamide. The solution was used to determine the TS2E3 content by high performance liquid chromatography. Device: Waters ACQUITY UPLC Chromatographic column: Waters BEH-C18 2.1×150 mm (manufactured by Waters)
[0073] (3) L-T2SE4 content The L-T2SE4 content was determined by HPLC using the same method as described above for the TS2E3 content determination.
[0074] (4) Intrinsic viscosity (IV) 0.1 g of a sample dried at 60°C for 24 hours was accurately weighed and dissolved in 25 mL of a mixed solvent of phenol / tetrachloroethane (3 / 2 (mass ratio)), and the intrinsic viscosity (IV) was measured at 30°C using an Ostwald viscometer.
[0075] (5) Number average molecular weight The number average molecular weight was measured by Waters gel permeation chromatography using a chloroform / hexafluoroisopropanol mixed solvent (volume ratio = 9 / 1) as a solvent and polystyrene as a measurement standard. The polystyrene-equivalent measured value was obtained using a chloroform / hexafluoroisopropanol mixed solvent (volume ratio = 9 / 1) as an eluent.
[0076] (6) Carboxyl terminal group concentration (AV) Accurately weigh 0.2g of a sample dried at 60°C for 24 hours, and set the weight at this time to W (g). Add 10ml of benzyl alcohol and the weighed sample to a test tube, immerse the test tube in an oil bath heated to 205°C, and dissolve the sample while stirring with a glass rod. Set the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes to A, B, and C, respectively. Then, prepare a new test tube, add only benzyl alcohol, and treat in the same order, and set the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes to a, b, and c, respectively. Use a 0.04mol / l potassium hydroxide solution (ethanol solution) with a known correction factor to titrate. Use phenolphthalein as the indicator, and determine the titration amount (ml) of the potassium hydroxide solution when the color changes from yellow-green to light red. Set the titration amount of samples A, B, and C to XA, XB, and XC (ml). Set the titration amount of samples a, b, and c to Xa, Xb, and Xc (ml). The titration amount XA, XB, and XC for each dissolution time are used to calculate the titration amount V (ml) when the dissolution time is 0 minutes by the least square method. Similarly, the titration amount V0 (ml) is calculated using Xa, Xb, and Xc. Then, AV is calculated according to the following formula 5. AV(eq / t)=[(V-V0)×NF×1000] / W (Formula 5) NF: Correction factor of 0.04 mol / l potassium hydroxide solution W: Sample weight (g)
[0077] (7) Hue (chromaticity b value and chromaticity L value) The chromaticity of the small piece of the copolyester resin was measured using a colorimeter (Model 1001DP, manufactured by Nippon Denshoku Co., Ltd.), and the chromaticity b value and chromaticity L value were determined.
[0078] (8) Melting point The measurement was performed using a differential scanning calorimeter (DSC) TAS100 thermal analysis system manufactured by TA Instruments. 7.5±0.3 mg of the polyester resin sample was added to an aluminum dish, heated to 280°C using a melting point determination device, maintained for 1 minute, and then rapidly cooled with liquid nitrogen. The sample was then heated from room temperature to 300°C at a heating rate of 20°C / minute to determine the melting point (Tm). Tm was taken as the temperature corresponding to the maximum value of each peak.
[0079] (9) Glass transition temperature (Tg) Using a differential scanning calorimeter (model: DSC220) manufactured by Seiko Instruments Inc., 5 mg of a sample was heated from -40°C to 120°C at a heating rate of 10°C / min, and the glass transition temperature was determined from the obtained endothermic curve. The temperature at the intersection of the extended line of the baseline below the glass transition temperature and the tangent line representing the maximum slope in the transition portion was set as the glass transition temperature (Tg).
[0080] (10) Aluminum atomic content 0.1 g of a sample was dissolved in a 6 M hydrochloric acid solution and allowed to stand for one day, then diluted with pure water to obtain a 1.2 M hydrochloric acid measurement solution. The aluminum atom content of the prepared solution sample was determined by high frequency plasma emission analysis.
[0081] (11) Phosphorus atomic content The phosphorus compound is converted into orthophosphoric acid by dry ashing decomposition of 1g sample in the presence of sodium carbonate, or wet decomposition with a mixture of sulfuric acid / nitric acid / perchloric acid or a mixture of sulfuric acid / hydrogen peroxide. Then, it is reacted with molybdate in a 1 mol / L sulfuric acid solution to obtain phosphomolybdic acid, which is reduced with hydrazine sulfate to generate heteropoly blue. The absorbance at a wavelength of 830nm is measured with an absorptiophotometer (manufactured by Shimadzu Corporation, UV-150-02). The amount of phosphorus atoms in the sample is quantified by a pre-made standard curve.
[0082] (12) Titanium atom content Weigh 1g of sample accurately in a platinum crucible and carbonize and ashed it in an electric furnace. Melt the residue with potassium hydrogen sulfate, dissolve the melt with dilute hydrochloric acid, and determine the content of tetrabutyl titanate (sometimes referred to as TBT) using diantipyryl methane colorimetry. The unit is titanium atoms, expressed in ppm.
[0083] (13) Antimony atomic content 1 g of the sample was wet decomposed with a mixture of sulfuric acid and hydrogen peroxide. Then, sodium nitrite was added to convert the antimony atoms into Sb 5+ Brilliant green was added to generate a blue complex with antimony. The complex was extracted with toluene and the absorbance at a wavelength of 625 nm was measured using an absorptiophotometer (manufactured by Shimadzu Corporation, UV-150-02). The amount of antimony atoms in the sample was quantitatively measured colorimetrically using a pre-prepared standard curve.
[0084] (14) Cobalt atomic content 1 g of the sample was decomposed by ash in a platinum crucible, and 6 mol / L hydrochloric acid was added to evaporate it to dryness. It was dissolved in 1.2 mol / L hydrochloric acid, and the luminescence intensity was measured using an ICP luminescence analyzer (manufactured by Shimadzu Corporation, ICPS-2000). The amount of cobalt atoms in the sample was quantified based on a pre-made standard curve.
[0085] (15) Lithium atom content Weigh 1g of sample in a platinum crucible and pre-carbonize on a heating plate to 400°C. Then, use the FO610 electric furnace manufactured by YAMATO Science Co., Ltd. to perform ashing treatment at 550°C for 8 hours. After ashing, add a small amount of 6.0N hydrochloric acid and hydrofluoric acid, perform acid decomposition on a heating plate, and heat treatment until the acid is completely volatilized. After the acid decomposition is completed, use 20mL of 1.2N hydrochloric acid to make the volume constant, use a high-frequency inductively coupled plasma luminescence analyzer (manufactured by Hitachi High-Technologies Co., Ltd., SPECTROBLUE) to measure the lithium concentration in the obtained test solution, and calculate the lithium content in the sample.
[0086] (16) Die head contamination and foreign matter adhesion The dried copolyester resin sample was put into an extruder equipped with a sheet die and formed into a sheet with a thickness of about 0.5 mm for two consecutive days. The state of contamination at the die outlet and the state of foreign matter attached to the sheet surface were evaluated visually according to the following criteria. (Evaluation Criteria) ◎: There is almost no contamination at the die outlet, and the sheet surface is in good condition ○: There is a small amount of contamination on the die outlet, but the surface of the sheet is in good condition Δ: There is a small amount of contamination attached to the die outlet, and a small amount of foreign matter attached to the surface of the sheet ×: The contamination at the die outlet is very serious, and there are a lot of foreign matter attached to the surface of the sheet
[0087] (17) Haze value The copolyester resin was melted at 280° C. using an injection molding machine (M-150C-DM manufactured by Meiki Seisakusho Co., Ltd.) and molded into a step-molded plate having a thickness of 2 to 11 mm at a mold temperature of 10° C. The haze value (%) of the 3 mm thick portion of the molded plate was measured using a haze meter (Model NDH2000 manufactured by Nippon Denshoku Co., Ltd.).
[0088] (18)DSC Using a YAMATO DP63 dryer, place the sample at 120°C for 120 minutes. Using a differential scanning calorimeter (DSC), heat the sample from -100°C to 300°C at 20°C / min, then cool it to -100°C at 50°C / min, and then heat it from -100°C to 300°C at 20°C / min. Confirm whether a melting peak is displayed during the two heating processes. Set "○" if no melting peak is displayed during the two heating processes, and set "×" if a melting peak is displayed in any one of them.
[0089] (19) Thermal stability evaluation: thermal oxidation decomposition parameter (TD) The intrinsic viscosity (IV) of the copolyester resin was measured and referred to as IV before the heating test ([IV]i). On the other hand, 3 g of a small piece of the dried copolyester resin was placed in a glass test tube and immersed in an oil bath at 280° C. for 120 minutes under a nitrogen atmosphere to melt it. The IV after heating ([IV]i) was measured. f1 ). By [IV] i and [IV] f1 , TD is calculated according to the following formula. TD=0.245{[IV] f1 -1.47 -[IV] i -1.47} The smaller the value of the thermooxidative decomposition parameter (TD) of the copolyester resin, the higher the thermal stability.
[0090] (20) Acetaldehyde (AA) content in polyester resin: The sample / distilled water = 1 gram / 2cc was added to a nitrogen-substituted glass ampoule, the upper part of the ampoule was sealed, and the extraction treatment was performed at 160°C for 2 hours. After cooling, the acetaldehyde content in the extract was measured by high-resolution gas chromatography, and the concentration was expressed in ppm. As an odor evaluation, the acetaldehyde content of 80 ppm or less was set as ◎, more than 80 ppm and less than 120 ppm was set as 0, more than 120 ppm and less than 160 ppm was set as Δ to 0, and more than 160 ppm was set as ×.
[0091] (Example 1) A slurry containing high-purity terephthalic acid (TPA), succinic acid (equivalent to an aliphatic acid having 4 carbon atoms) and sodium dimethyl sulfoisophthalate (GCM) as dicarboxylic acid components and ethylene glycol (EG) and diethylene glycol (DEG) as diol components is prepared so that the resin composition is as shown in Table 1. The molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is adjusted to 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which the reactants have previously remained. Next, the esterification reaction is carried out under stirring, a tank pressure of 0.15 MPa, and 257°C in a manner such that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and the esterification reaction is carried out under the conditions of a tank pressure of 0.05 MPa, stirring, and 257°C in a manner such that the average residence time is 1 hour. Then, the obtained reaction product was transferred to the third esterification reaction tank, and an esterification reaction was carried out under stirring at a tank internal pressure of 0.05 MPa and 257°C.
[0092] To the produced oligomer, diethylene glycol in an amount corresponding to the target composition was added in an amount equivalent to 20% of the amount added before the esterification reaction, and the mixture was stirred for 15 minutes to allow the reaction to proceed.
[0093] To the esterification reaction product, a certain amount of ethylene glycol solution of an aluminum compound (basic aluminum acetate) and an ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added as polymerization catalysts, and continuously supplied to the first polycondensation reaction tank, and polycondensation reaction was carried out under stirring at 261°C and 6.7 kPa for 1 hour, then under stirring at 272°C and 0.6 kPa for 1 hour in the second polycondensation reaction tank, and further under stirring at 275°C and 0.10-0.20 kPa for 1 hour in the final polycondensation reaction tank. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted in a linear form from the nozzle of the die head, cooled in a cooling bath, and cut into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0094] (Examples 2 to 4) Examples 2 to 4 are examples in which the amount of sodium sulfoisophthalate (GCM) was changed. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol, and diethylene glycol was changed so that the resin composition had the values shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0095] (Examples 5 and 6) Examples 5 and 6 are examples in which the amount of diethylene glycol (DEG) was changed. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol, and diethylene glycol was changed so that the resin composition had the values shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0096] (Examples 7 to 9) Examples 7 to 9 are examples in which the number average molecular weight and / or the carboxyl terminal group concentration (AV) were changed. Specifically, the copolyester resin was obtained in the same manner as in Example 1 except that the reaction conditions (average residence time of the esterification reaction) were adjusted so that the number average molecular weight and / or the carboxyl terminal group concentration (AV) were the values shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0097] (Examples 10 to 12) Examples 10 to 12 are examples in which the amount of the aluminum compound and / or phosphorus compound of the polymerization catalyst is changed. Specifically, the copolyester resin was obtained in the same manner as in Example 1 except that the amount of the aluminum compound and / or phosphorus compound added was adjusted so that the amount of the residual aluminum atoms and / or phosphorus atoms was the value shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0098] (Examples 13-14) Examples 13 to 14 are examples of further blending lithium acetate into the slurry in order to improve the odor by reducing the acetaldehyde content in the polymer. Specifically, a slurry containing high-purity terephthalic acid (TPA) and sodium dimethyl sulfoisophthalate (GCM) as dicarboxylic acid components, ethylene glycol (EG) and diethylene glycol (DEG) as diol components, and lithium acetate is prepared in such a manner that the resin composition has the values shown in Table 1. Among them, the molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is adjusted to 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which the reactants have previously remained. Bonding, esterification reaction is carried out under stirring, a tank pressure of 0.15 MPa, and 257°C in a manner such that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and an esterification reaction is carried out under a tank pressure of 0.05 MPa, stirring, and 257°C in a manner such that the average residence time is 1 hour. Then, the obtained reaction product was transferred to the third esterification reaction tank, and an esterification reaction was carried out under stirring at a tank internal pressure of 0.05 MPa and 257°C.
[0099] To the produced oligomer, diethylene glycol in an amount corresponding to the target composition was added in an amount equivalent to 20% of the amount added before the esterification reaction, and the mixture was stirred for 15 minutes to allow the reaction to proceed.
[0100] To the esterification reaction product, a certain amount of ethylene glycol solution of an aluminum compound (basic aluminum acetate) and an ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added as polymerization catalysts, and continuously supplied to the first polycondensation reaction tank, and polycondensation reaction was carried out under stirring at 261°C and 6.7 kPa for 1 hour, then under stirring at 272°C and 0.6 kPa for 1 hour in the second polycondensation reaction tank, and further under stirring at 275°C and 0.10-0.20 kPa for 1 hour in the final polycondensation reaction tank. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted in a linear form from the nozzle of the die head, cooled in a cooling bath, and cut into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0101] (Example 15) Example 15 is an example of using antimony compounds and cobalt compounds instead of aluminum compounds as polymerization catalysts. Specifically, a slurry containing high-purity terephthalic acid (TPA) and sodium dimethyl sulfoisophthalate (GCM) as dicarboxylic acid components and ethylene glycol (EG) and diethylene glycol (DEG) as diol components is prepared in such a way that the resin composition has the values shown in Table 1. Among them, the molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is adjusted to 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which the reactants have remained in advance. Then, the esterification reaction is carried out under stirring, a tank pressure of 0.15MPa, and 257°C in such a way that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and an esterification reaction is carried out under the conditions of a tank pressure of 0.05MPa, stirring, and 257°C in such a way that the average residence time is 1 hour. Then, the obtained reaction product was transferred to the third esterification reaction tank, and an esterification reaction was carried out under stirring at a tank internal pressure of 0.05 MPa and 257°C.
[0102] To the produced oligomer, diethylene glycol in an amount corresponding to the target composition was added in an amount equivalent to 20% of the amount added before the esterification reaction, and the mixture was stirred for 15 minutes to allow the reaction to proceed.
[0103] To the esterification reaction product, a certain amount of ethylene glycol solution of an antimony compound (antimony trioxide), an ethylene glycol solution of a cobalt compound (cobalt acetate) and an ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added as polymerization catalysts, and continuously supplied to the first polycondensation reaction tank, and polycondensation reaction was carried out under stirring at 261°C and 6.7 kPa for 1 hour, then under stirring at 272°C and 0.6 kPa for 1 hour in the second polycondensation reaction tank, and further under stirring at 275°C and 0.10-0.20 kPa for 1 hour in the final polycondensation reaction tank. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted in a linear form from the nozzle of the die head, cooled in a cooling bath, and cut into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0104] (Examples 16 and 17) Examples 16 and 17 are examples of using a titanium compound instead of an aluminum compound as a polymerization catalyst. Specifically, a slurry containing high-purity terephthalic acid (TPA) and sodium dimethyl sulfoisophthalate (GCM) as dicarboxylic acid components, ethylene glycol (EG) and diethylene glycol (DEG) as diol components, and lithium acetate is prepared in such a manner that the resin composition has the values shown in Table 1. Among them, the molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is adjusted to 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which reactants have previously remained. Next, an esterification reaction is carried out under stirring, a tank pressure of 0.15 MPa, and 257°C in such a manner that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and an esterification reaction is carried out under the conditions of a tank pressure of 0.05 MPa, stirring, and 257°C in such a manner that the average residence time is 1 hour. Then, the obtained reaction product was transferred to the third esterification reaction tank, and an esterification reaction was carried out under stirring at a tank internal pressure of 0.05 MPa and 257°C.
[0105] To the produced oligomer, diethylene glycol in an amount corresponding to the target composition was added in an amount equivalent to 20% of the amount added before the esterification reaction, and the mixture was stirred for 15 minutes to allow the reaction to proceed.
[0106] A certain amount of 1-butanol solution of tetrabutyl titanate (TBT) and ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the aforementioned chemical formula (4)) were added to the esterification reaction product as a polymerization catalyst, and the mixture was continuously supplied to the first polycondensation reaction tank, and the reaction was carried out under stirring at 261°C and 6.7 kPa for 1 hour, and then in the second polycondensation reaction tank, the reaction was carried out under stirring at 272°C and 0.6 kPa for 1 hour, and further in the final polycondensation reaction tank, the reaction was carried out under stirring at 275°C and 0.10-0.20 kPa for 1 hour. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted in a linear form from the nozzle of the die head, cooled in a cooling bath, and sheared into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0107] (Examples 18 and 19) Examples 18 and 19 are examples in which titanium oxide is further blended in order to improve colorability. Specifically, except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol and diethylene glycol, the type and amount of the polymerization catalyst, the carboxyl terminal group concentration (AV) or the number average molecular weight are changed to the values shown in Table 1, lithium acetate is further blended into the slurry, and titanium oxide CR930 (manufactured by Ishihara Sangyo) is added simultaneously with the polymerization catalyst in an amount of 0.5 ppm (Example 20) or 12000 ppm (Example 21) relative to the polyester resin, a copolyester resin is obtained in the same manner as in Example 1. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0108] (Examples 20 and 21) Examples 20 and 21 are examples in which a toner is further blended to improve colorability. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol and diethylene glycol, the type and amount of the polymerization catalyst, the carboxyl terminal group concentration (AV) or the number average molecular weight were changed to the values shown in Table 1, and Solvent Blue 45 (manufactured by Clariant) was further added as a toner in an amount of 0.1 ppm (Example 22) or 50 ppm (Example 23) relative to the polyester resin at the same time as the polymerization catalyst. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0109] (Examples 22 and 23) Examples 22 and 23 are examples in which the type of aliphatic acid having 2 to 4 carbon atoms is changed. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that succinic acid (equivalent to an aliphatic acid having 4 carbon atoms) was changed to oxalic acid (equivalent to an aliphatic acid having 2 carbon atoms) (Example 22) or malonic acid (equivalent to an aliphatic acid having 3 carbon atoms) (Example 23). The evaluation results of the obtained copolyester resin are shown in Table 1.
[0110] (Examples 24 and 25) Examples 24 and 25 are examples in which the amount of the aliphatic acid having 2 to 4 carbon atoms was changed. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, succinic acid (equivalent to the aliphatic acid having 4 carbon atoms), sulfoisophthalic acid, ethylene glycol and diethylene glycol was changed to the value shown in Table 1 in the resin composition. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0111] (Comparative Example 1) Comparative Example 1 is an example in which sodium sulfoisophthalate (GCM) is not used as a dicarboxylic acid component and only terephthalic acid is used. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, ethylene glycol and diethylene glycol was changed to the value shown in Table 1 in the resin composition. The evaluation results of the obtained copolyester resin are shown in Table 1. In addition, in Comparative Example 1, since GCM was not used, the TS2E3 amount and the L-T2SE4 amount were not measured.
[0112] (Comparative Example 2) Comparative Example 2 is an example in which the amount of sodium sulfoisophthalate (GCM) is too small. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol and diethylene glycol was changed to the values shown in Table 1 for the resin composition. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0113] (Comparative Example 3) Comparative Example 3 is an example in which the amount of sodium sulfoisophthalate (GCM) is too large. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol and diethylene glycol was changed to the values shown in Table 1 for the resin composition. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0114] (Comparative Example 4) Comparative Example 4 is an example in which the amount of diethylene glycol (DEG) is too large. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol and diethylene glycol was changed to the values shown in Table 1 for the resin composition. The evaluation results of the obtained copolyester resin are shown in Table 1.
[0115] [Table 1]
[0116] As can be seen from Table 1, in Examples 1 to 25 that meet all the conditions of the present invention, there is no die contamination and foreign matter adhesion, and the transparency (haze value, DSC measurement) is also excellent, and the recyclability (thermal stability) is also excellent. In contrast, since Comparative Example 1 does not use sodium sulfoisophthalate (GCM) as a dicarboxylic acid component but only uses terephthalic acid, the amount of sodium sulfoisophthalate (GCM) in Comparative Example 2 is too small, so the transparency (haze value, DSC measurement) is poor and the recyclability (thermal stability) is poor. Since the amount of sodium sulfoisophthalate (GCM) in Comparative Example 3 is too much, the content of by-product oligomers (TS2E3, L-T2SE4) is high, so there are many cases of die contamination and foreign matter adhesion. Since the amount of diethylene glycol (DEG) in Comparative Example 4 is too much, the recyclability (thermal stability) is poor and the chromaticity b value is high. Industrial Applicability
[0117] The copolyester resin of the present invention has the advantages of transparency and moldability brought about by the use of diethylene glycol and sodium sulfoisophthalate, and when continuously producing products such as films, molded products, and fibers, there is almost no die contamination and foreign matter adhesion to the products, and there is no resin coloring and molecular weight reduction during recycling. Therefore, the present invention has made a great contribution to the industry.
Claims
1. A copolyester resin, characterized in that: The invention relates to a copolymerized polyester resin containing terephthalic acid as a main dicarboxylic acid component and ethylene glycol as a main diol component; in all the polyester resin components, when the total amount of the dicarboxylic acid component is 100 mol%, the ratio of the terephthalic acid component to the total dicarboxylic acid components is 79.95-94.95 mol%, the ratio of the aliphatic acid having 2 to 4 carbon atoms to the total dicarboxylic acid components is 5 to 20 mol%, the ratio of sodium sulfoisophthalate to the total dicarboxylic acid components is 0.05 to 10 mol%, and when the total amount of the diol component is 100 mol%, the ratio of diethylene glycol to the total diol components is 1 to 22 mol%, the content of free cyclic monomers composed of terephthalic acid, sodium sulfoisophthalate and ethylene glycol is 40 ppm or less, and the content of free linear oligomers composed of terephthalic acid, sodium sulfoisophthalate and ethylene glycol is 60 ppm or less.
2. The copolyester resin according to claim 1, characterized in that The chromaticity b value is -5.0 to 15.
0.
3. The copolyester resin according to claim 1, characterized in that The carboxyl terminal group concentration AV is 3 to 25 eq / t.
4. The copolyester resin according to claim 1, characterized in that The copolyester resin contains aluminum atoms and phosphorus atoms. The content of aluminum atoms in the copolyester resin is 15 to 40 ppm. The molar ratio of phosphorus atoms to aluminum atoms in the copolyester resin is greater than 0 and less than 2.
6.
5. The copolyester resin according to claim 1, characterized in that The copolyester resin further contains alkali metal atoms and / or alkaline earth metal atoms derived from alkali metal compounds and / or alkaline earth metal compounds other than sodium sulfoisophthalate, and the content of the alkali metal atoms and / or alkaline earth metal atoms in the copolyester resin is 1 to 100 ppm.
6. The copolyester resin according to any one of claims 1 to 5, characterized in that The step-molded plate obtained by molding the copolyester resin has a haze value of 10% or less in a portion having a thickness of 3 mm.
7. A molded product, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.
8. A heat shrinkable film, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.
9. A fiber, characterized in that Contains the copolyester resin according to any one of claims 1 to 5.
10. A nonwoven fabric, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.
11. An adhesive, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.
12. A coating, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.
Citation Information
Patent Citations
JP1971014963Y1
JP1973007952U
Waterrservice installation
JP1978045749A
Sulfonated aliphatic-aromatic copolyesters and shaped articles made therefrom
JP2007500769A
Aliphatic-aromatic polyester and article produced from the same
JP2010150542A